Preliminary Research: Utilization of Gourami Fish Bone Flour (Osphronemus gouramy) in Making Calcium Dumplings - Dwi Lestari Handayani; Monicha Efi Sumaimi; Tri Ani Ashari; Jumadi Jumadi (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightKnowing the amount of daily calcium neededKnowing utilization of fish bone meal and its processed productsAnalysis of the most preferred types of food and fish speciesAbstractGourami (Osphronemus gouramy) is a type of freshwater fish native to Indonesia that is widely preferred, and has high economic value so that production per year increases. Increasing the amount of fish production will result in an increased amount of fish bone waste. However, the processing of gourami in general is still limited to using the meat for frying, grilling, filling, and making shredded fish, while the fish bones are not widely used. Several studies have shown that fish bones that are made into flour contain high calcium. Food processing from fish bone flour can be used as an alternative to meet daily calcium intake. Several stud- ies have started to use fish bone flour to become processed food with calcium such as baked donuts, starch balls, and biscuits, but there are still many other foods from the different regions that need to utilize the fish bone as one of their ingredi- ents. The purpose of this study was to analyze the understanding of the community members, and newcomers in Purbalingga regarding the use of fish bone flour, and its processed products, calcium content, also to know their favorite snacks, and types of fish. The results of the survey analysis stated that it is necessary to use Gourami fish bone flour in making calcium dumplings and its resistance to oxygen.